Meninjau Ulang Sustainable Development: Kajian Filosofis Atas Dilema Pengelolaan Lingkungan Hidup di Era Post Modern - Lailiy Muthmainnah; Rizal Mustansyir; Sindung Tjahyadi (Jurnal Filsafat "WISDOM", 2020)
This study is an attempt to re-question the base arguments forsustainable developmentproposal with regardto environmental management. This attempt is important considering intensive deploymemt of cost and benefit calculations in every environmental management policy, which rooted in the utilitarian philosophical tradition. This research runs in the area of political philosophyandemploys methodical components includingdescription, interpretation, critical analysis, and verstehen. The current research suggests that the emergence of sustainable development as a concept of environment management goes along with modernity with all issues that it brings. The proposal of sustainable developments can be categorized into constructive postmodernismapproach. The main purpose of this proposal is to create a condition of balance between the needs of the present generation and the adequacy of the needs of the future generations. However, the concept appears to raise a new concern considering the meaning of “sustainability”has become contestation with strong tendency to economicconsideration which reduces the calculation of cost-benefits into cash-value calculations. This reductionis tendency leads to a dilemma considering the aspiration of shiftinganthropocentrism to ecocentrismunderlying behind concept of sustainable development will ironically produce a new forms of anthropocentrism.